The Effectiveness of X Herbal Medicine On The Reducing Blood Sugar In A Diabetic Mice Model - Purwaeni Purwaeni; Nurbaiti Fentiani Siahaan; Meilinda Windy Astuty (International Journal of Health and Pharmaceutical (IJHP), 2025)
The prevalence of Diabetes Mellitus in Indonesia is estimated to reach 21.3 million people by 2030. Treatment with oral antidiabetic drugs carries the risk of myocardial infarction and congestive heart failure, while modern therapy of NIDDM has adverse side effects. WHO recommends researching traditional methods, especially plants with hypoglycemic effects. Efficacy claims in herbal medicines, especially herbal medicines, are rarely reported, so it is necessary to test antidiabetic activity to ensure their use. To determine the antidiabetic activity of herbal medicine product X on blood sugar levels in aloxane-induced mice (Mus Musculus), determine the most effective dose, and determine the decrease in GDP after the administration of herbal medicine X on days 7 and 14. Experimental research uses male mice (Mus Musculus) as test animals. Blood glucose levels were measured before and after treatment, with a negative control of CMC-Na of 0.5% and a positive control of glibenclamide of 0.65mg/Kg BB. The optimal dose of herbal product X is determined by a ratio of doses of 52 mg/KgBB, 104 mg/KgBB, and 156 mg/KgBB for 7 to 14 days. Herbal Medicine X at doses of 52mg/KgBB, 104mg/KgBB, and 156mg/KgBB succeeded in reducing aloxan-induced blood sugar levels in mice. The dose of 156mg/KgBB was found to be the optimal dose based on the Mann-Whitney test with Sig<0.05. The most significant decline on day 14 was based on the Kruskal Wallis test with Sig<0.05. Herbal Medicine X was effective in lowering blood sugar levels in mice, with an optimal dose of 156mg/Kg BB and a significant decrease on day 14.